Silicon-organic hybrid photonics: an overview of recent advances, electro-optical effects and CMOS integration concepts. (2nd April 2021) - Steglich, Patrick; Mai, Christian; Villringer, Claus; Dietzel, Birgit; Bondarenko, Siegfried; Ksianzou, Viachaslau; Villasmunta, Francesco; Zesch, Christoph; Pulwer, Silvio; Burger, Martin; Bauer, Joachim; Heinrich, Friedhelm; et al.
Abstract: In recent decades, much research effort has been invested in the development of photonic integrated circuits, and silicon-on-insulator technology has been established as a reliable platform for highly scalable silicon-based electro-optical modulators. However, the performance of such devices is restricted by the inherent material properties of silicon. An approach to overcoming these deficiencies is to integrate organic materials with exceptionally high optical nonlinearities into a silicon-on-insulator photonic platform. Silicon–organic hybrid photonics has been shown to overcome the drawbacks of silicon-based modulators in terms of operating speed, bandwidth, and energy consumption. This work reviews recent advances in silicon–organic hybrid photonics and covers the latest improvements to single components and device concepts. Special emphasis is given to the in-device performance of novel electro-optical polymers and the use of different electro-optical effects, such as the linear and quadratic electro-optical effect, as well as the electric-field-induced linear electro-optical effect. Finally, the inherent challenges of implementing non-linear optical polymers on a silicon photonic platform are discussed and a perspective for future directions is given.